Experimental study on the mechanical and tribological characteristics of pineapple leaf fiber reinforced polymer composites for biomedical applications (Fracture and Structural Integrity, 2026)
New biomedical supportive and lightweight structures require the creation of sustainable polymer composites of high strength and wear resistance. This research explores the use of alkali-treated pineapple leaf fiber (PALF) reinforced epoxy composites and determines complete structure property wear relationships using combined mechanical, tribological, and microstructural analysis. The novelty of the work is based on the correlation of fiber content with the stiffness increment, the damage tolerance, and degradation behavior under friction conditions at controlled fabrication conditions. A hand lay-up method was used to manufacture composite laminates with 5-25 wt.% PALF. The tensile strength rose to 78 MPa and Youngs modulus rose to 3.5 GPa. Flexural strength increased to 112 MPa and flexural modulus to 3.7 GPa. The energy impact decreased by 12 and dropped to 20 kJ/m2 and Shore D hardness rose by 72 and 76, respectively, which means the increase in deformation and surface damage resistance. Tribological testing revealed that coefficient of friction and wear rate decreased to 0.51 and 3.7 x 10-6 mm 3/N-m respectively by fiber-supported load distribution and establishment of protective transfer films. The scanning electron microscopy showed that there was consistent fiber dispersion, good bonding of fiber matrix, and predominance of crack-bridging and pull-out processes involving the fracture resistance. The best mechanical tribological behavior was observed with a concentration of 10-15 wt.% PALF. A further study will involve biocompatibility studies, long-lasting stability, and surface functionalization to permit biomedical assistance elements like orthotic braces, prosthetic frames, and non-load-bearing auxiliary medical components.
Keywords: Pineapple leaf fiber composites; Natural fiber reinforced polymers; Mechanical performance; Wear and friction behavior; Biocompatible materials; Sustainable biomedical composites